2018
DOI: 10.1371/journal.pone.0192674
|View full text |Cite
|
Sign up to set email alerts
|

A thioredoxin-dependent peroxiredoxin Q from Corynebacterium glutamicum plays an important role in defense against oxidative stress

Abstract: Peroxiredoxin Q (PrxQ) that belonged to the cysteine-based peroxidases has long been identified in numerous bacteria, but the information on the physiological and biochemical functions of PrxQ remain largely lacking in Corynebacterium glutamicum. To better systematically understand PrxQ, we reported that PrxQ from model and important industrial organism C. glutamicum, encoded by the gene ncgl2403 annotated as a putative PrxQ, played important roles in adverse stress resistance. The lack of C. glutamicum prxQ g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 61 publications
1
57
0
Order By: Relevance
“…Afterwards, the generated TPx-Q is ready for another catalytic cycle. Su et al (30) indicated that the two cysteine residues are essential for enzymatic activity by mutation analysis. Furthermore, they proved that C. glutamicum TPx-Q catalytically eliminates peroxides by exclusively receiving electrons from Trx/TrxR system (30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Afterwards, the generated TPx-Q is ready for another catalytic cycle. Su et al (30) indicated that the two cysteine residues are essential for enzymatic activity by mutation analysis. Furthermore, they proved that C. glutamicum TPx-Q catalytically eliminates peroxides by exclusively receiving electrons from Trx/TrxR system (30).…”
Section: Discussionmentioning
confidence: 99%
“…Su et al (30) indicated that the two cysteine residues are essential for enzymatic activity by mutation analysis. Furthermore, they proved that C. glutamicum TPx-Q catalytically eliminates peroxides by exclusively receiving electrons from Trx/TrxR system (30). Unlike the typical 2-Cys Prx proteins, TPx-Q may exist as monomers, dimers, or a mixture (52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These phenomena suggested important functions of Trxs and PDIs. Previously, trx1 and trxR1 were shown to play an important role in reducing mycothiol peroxidase (MPx)\thiol peroxidase (Prx)\ methionine sulfoxide reductase A (MsrA)\peroxiredoxin Q (PrxQ) in C. glutamicum (Si et al, 2015a;Si et al, 2017;Si et al, 2015b;Su et al, 2018).…”
Section: Introductionmentioning
confidence: 99%